(untitled) (Global Journal of Medical Research, 2023)
Objective We have evaluated the value of using the ultrasound and mammographic features of primary breast malignancy to predict axillary lymph node metastasis in patients with known biopsy proven breast cancer We also determined the impact of demographic factors and various histopathological features of breast cancer on axillary lymph nodes metastasis Methods This descriptive retrospective study was an institutional review board-approved study with a waiver of informed consent Imaging features from 354 patients with digital mammogram and preliminary sonography and histopathological features of invasive breast carcinomas between March 2021 and August 2022were compared with axillary lymph node status for the presence of metastases We did univariate and multivariate logistic regression analysis for this purpose